2010
DOI: 10.1083/jcb.200910136
|View full text |Cite
|
Sign up to set email alerts
|

I-BAR protein antagonism of endocytosis mediates directional sensing during guided cell migration

Abstract: Although directed cellular migration facilitates the coordinated movement of cells during development and repair, the mechanisms regulating such migration remain poorly understood. Missing-in-metastasis (MIM) is a defining member of the inverse Bin/Amphiphysin/Rvs domain (I-BAR) subfamily of lipid binding, cytoskeletal regulators whose levels are altered in a number of cancers. Here, we provide the first genetic evidence that an I-BAR protein regulates directed cell migration in vivo. Drosophila MIM (dmim) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 61 publications
1
61
2
Order By: Relevance
“…Hence, our data together with other studies demonstrate that MIM is implicated in the membrane dynamics of endocytic vesicles. In addition to its association with endosomes, MIM has been also implicated in antagonizing the complex of cortactin and the CD2-associated protein, and in inhibition of the endocytosis of EGF and in directional border cell migration in Drosophila (Quinones et al, 2010). The difference between our observations and that report may reflect the multiple roles of MIM in endocytosis under different contexts, as described in these studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Hence, our data together with other studies demonstrate that MIM is implicated in the membrane dynamics of endocytic vesicles. In addition to its association with endosomes, MIM has been also implicated in antagonizing the complex of cortactin and the CD2-associated protein, and in inhibition of the endocytosis of EGF and in directional border cell migration in Drosophila (Quinones et al, 2010). The difference between our observations and that report may reflect the multiple roles of MIM in endocytosis under different contexts, as described in these studies.…”
Section: Discussioncontrasting
confidence: 57%
“…CINDR has three SH3 domains and positively regulates receptor-mediated endocytosis (29). Kometani et al (30) demonstrated that CIN85 functions upstream of IKKβ in the activation of NF-κB in B cells and is responsible for T-cell-independent type II antibody responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a Drosophila I-BAR domain protein that is related to mouse MIM and ABBA was shown to interact with this actin-binding protein to promote directional cell migration (Lin et al, 2005;Quinones et al, 2010). We thus generated a MIM construct where the previously identified cortactin-binding site was deleted (Lin et al, 2005).…”
Section: Mim Promotes Actin and Membrane Dynamics At Adherens Junctiomentioning
confidence: 99%